A comparative analysis of using cage acrossing the vertebral ring apophysis in normal and osteoporotic models under endplate injury: a finite element analysis - Wang, Jian; Geng, Ziming; Ma, Xiang; Zhang, Zepei; Miao, Jun (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Lateral lumbar fusion is an advanced, minimally invasive treatment for degenerative lumbar diseases. It involves different cage designs, primarily varying in size. This study aims to investigate the biomechanics of the long cage spanning the ring apophysis in both normal and osteoporotic models, considering endplate damage, using finite element analysis. Methods: Model 1 was an intact endplate with a long cage spanning the ring apophysis. Model 2 was an endplate decortication with a long cage spanning the ring apophysis. Model 3 was an intact endplate with a short cage. Model 4 was an endplate decortication with a short cage. On the basis of the four original models, further osteoporosis models were created, yielding a total of 8 finite element models. The provided passage delineates a study that elucidates the utilization of finite element analysis as a methodology to simulate and analyze the biomechanical repercussions ensuing from the adoption of two distinct types of intervertebral fusion devices (cages) within the physiological framework of a human body. Results: The investigation found no appreciable changes between Models 1 and 2 in the range of motion (ROM) at the fixed and neighboring segments, the L3-4 IDP, screw-rod stress, endplate stress, or stress on the trabecular bone of the L5. Increases in these stresses were seen in models 3 and 4 in the ranges of 0.4% to 676.1%, 252.9% to 526.9%, 27.3% to 516.6%, and 11.4% to 109.3%, respectively. The osteoporotic models for scenarios 3 and 4 exhibit a similar trend to their respective normal bone density models.In particular, except for L3-4 IDP, the maximum values of these parameters in osteoporotic Models 3 and 4 were much higher than those in normal bone quality Models 1 and 2, rising by 385.3%, 116%, 435.1%, 758.3%, and 786.1%, respectively. Conclusion: Regardless of endplate injury or osteoporosis, it is advised to utilize a long cage that is 5mm longer on each side than the bilateral pedicles because it has good biomechanical features and may lower the likelihood of problems after surgery. Additionally, using Long cages in individuals with osteoporosis may help avoid adjacent segment disease.